Detailed scattering contributions of different ocean water types to multiangle, polarimetric spaceborne observations in the UV-NIR regime - Ottaviani, Matteo; Chowdhary, Jacek (Frontiers in Remote Sensing, 2025)
Global retrievals of ocean parameters greatly benefit from spaceborne missions equipped with passive multispectral, multiangle and polarimetric capabilities. Here we present a compendium of advanced radiative transfer simulations of  such observations at the top of the atmosphere, where the total reflectance and its polarization counterpart are partitioned among the scattering contributions from the atmosphere, a rough ocean surface, and the ocean body. The focus is on the spectral contributions of different water types in an extensive wavelength range, which impact the retrievability of their descriptive parameters. Beside accurately quantifying such contributions for observations in heritage ocean-color bands, the results highlight the detectability of the ocean signal in the total reflectance measured in the ultraviolet range of the spectrum. Also, polarization signatures emerge for highly-complex waters in the green region and at larger wavelengths. This textbook exercise in radiative transfer provides the basis for a correct interpretation of spaceborne measurements, and can be exploited in studies related to instrument design and spectral information content.